ANALISIS PENGARUH INOVASI PRODUK,PERSEPSI HARGA DAN KUALITAS PRODUK TERHADAP KEPERCAYAAN PRODUK YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN KONSUMEN (Studi Kasus pada â€œAtala Artâ€ di Jepara) - Zulhelmi, Zulhelmi; Santoso, Suryono Budi (Faculty of Economics and Business Diponegoro University, 2018)
Decrease in purchasing decisions on a product may cause a decrease in the value of its sale. The same thing happened at Atala Art, a company engaged in furniture and creative crafts in Jepara, Central Java, is experiencing a decline in product sales in recent years. Strategic steps need to be taken to overcome this phenomenon.The research was conducted by using independent variables including product innovation, price perception and product quality; intervening variable that is product trust and dependent variable that is purchasing decision. The data were collected on the sample using the questionnaire method. Data were analyzed by chi-square test method, descriptive three-box method and multiple linear regression analysis.The results stated that respondents, representing most consumers have income of 0-5 million rupiahs, work as self-employed and civil servants with age range 31-40 years. Consumer valuation on product innovation and product trust have high score 80,00% and79,67% respectively compared to price perception (74,60%) and product quality (74,27%), purchase decision (74,27%) With the calculation of multiple linear regression, it can be concluded that product innovation, price perception and product quality have a significant influence on product trust, as well as product trust have a significant effect on purchasing decision.